2016
DOI: 10.4103/2277-9175.187400
|View full text |Cite
|
Sign up to set email alerts
|

Nasal carriage screening of community-associated methicillin resistant Staphylococcus aureus in healthy children of a developing country

Abstract: Background:The rapid emergence and spread of community-associated methicillin-resistant Staphylococcus aureus (CA-MRSA) has raised considerable public health concern in both developed and developing countries. The current study aimed to address the extent of this phenomenon in healthy preschool children of a developing country.Materials and Methods:We conducted a prospective study from April 2013 to March 2014 on 410 healthy 2-6 years old preschool children in Isfahan, Iran. Demographic medical data and nasal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 34 publications
2
10
2
1
Order By: Relevance
“…Several studies showed that sociodemographic characteristics and risk factors contribute a lot to the nasal carriage of S. aureus and MRSA [5, 21, 22, 24, 25, 27, 28]. The result of this study showed children's father's educational status significantly associated with nasal carriage of S. aureus which was in contrast with a study in Nigeria [12].…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…Several studies showed that sociodemographic characteristics and risk factors contribute a lot to the nasal carriage of S. aureus and MRSA [5, 21, 22, 24, 25, 27, 28]. The result of this study showed children's father's educational status significantly associated with nasal carriage of S. aureus which was in contrast with a study in Nigeria [12].…”
Section: Discussioncontrasting
confidence: 97%
“…This finding of MRSA nasal carriage was in line with the reports of Iraq (11.1%) [23] and higher than the reports in Serbia (7.55%), Ghana (1.6%), Italy (1.54%), India (3.17%), and Jordan (7.1%) [16, 17, 20, 21, 27]. However, this MRSA nasal carriage was lower than the reports in Iran (21.74%), Nigeria (59.1%), Iraq (13.3%), Vietnam (12.3%), Jimma (18.8%), and Bahir Dar (13.8%) [18, 19, 22, 24, 25, 28]. This variation might be due to the difference in the diagnostic techniques which was used to confirm/detect MRSA other than cefoxitin disc detection method.…”
Section: Discussionmentioning
confidence: 95%
“…Detection of the epidemiology, clinical syndrome, and antibiotic resistance of possible CA-MRSA allows early initiation of treatment and control measures (21,22). The prevalence of HA-MRSA in the present study was 77.7% (n = 42), which is high.…”
Section: Discussionmentioning
confidence: 52%
“…[20212223242526] The level of resistance against erythromycin among MRSA species isolated in the current study was 50%; hence, using this antibiotic to control infections caused by these bacteria is not recommended.…”
Section: Discussionmentioning
confidence: 99%